PENYELESAIAN SENGKETA TERHADAP RISIKO YANG DIHADAPI PEMODAL PADA SECURITIES CROWDFUNDINGDI INDONESIA - Nur Indah Putri Ramadhani (Magister Hukum Pascasarjana Universitas Semarang, 2021)
This study aims to analyze the Financial Services Authority Regulation (POJK)Number 57 of 2020's position concerning Securities Offering Through Information Technology-Based Crowdfunding Services in the Legislative System in Indonesia in regulating securities crowdfunding and resolving disputes regarding the risks faced by investors in securities crowdfunding in Indonesia. Securities crowdfunding itself is an improvement of equity crowdfunding which has been running in Indonesia. In the process of the improvement, the revision of Financial Services Authority Regulation number 37 of 2018 about equity crowdfunding to become the Financial Services Authority Regulation number 57 of 2020 about securitiescrowdfunding by Financial Services Authority (OJK) induced by an imperfection in the running of equity crowdfunding. Equity crowdfunding is unable to be maximally utilized by small and medium businesses (UKM) as well as start-up companies because both of them are not considered limited companies (PT). The securities issuance of small and medium businesses as well as start-up companies are also fixed in the form of shares sale. The research method used is normative juridical with a statute approach and conceptual approach. The statute approach uses POJK 57/2020, and the conceptual approach uses Hans Nawiansky's theory of theorie von stufenufbau der rechtsordnung. The results of the study conclude that first, based on the theory of theorie von stufenufbau derrechtsordnungfrom Hans Nawiasky, the position of POJK in the arrangement of state legal norms is as Verordnungor implementing regulations, and POJK has binding legal force and the legal consequence is that all forms of security crowdfunding practices inIndonesia are subject to and comply with the provisions of POJK 57/2020. Second, regarding the risks faced by investors, dispute resolution can be solved in three ways, namely through internal dispute resolution, external dispute resolution, and courts.